PENGARUH DUKUNGAN KELUARGA DAN DUKUNGAN KONSELOR ADIKSI TERHADAP MOTIVASI UNTUK SEMBUH PADA PECANDU NARKOBA DIBALAI REHABILITASI BNN BADDOKA MAKASSAR - Ernawati, Ernawati; Qasim, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2018)
In 2014 the number of drug abusers in Indonesia is estimated about 3,8 to 4,1 million people who have used drugs within a year in the group age around 10-59 years old, in other words, there is about 1 of 44 to 48 people of them which is 10-59 years old who still or ever used drugs in 2014. The purpose of this research is to know the influence of family and counselor support on motivation to recover of the drug addicts in rehabilitation center of BNN Baddoka Makassar. This research used an analytical observational with cross sectional approach. The research was conducted at BNN Baddoka Rehabilitation center in Makassar on May – July 2017. The number of population was 123 people and the number of sample was 55 respondents. The sampling technique used purposive sampling. The sampling technique used purposive sampling. The data collection used questionnaire and Chi-square statistical test was used in the data processing. Based on the statistical test result, there were influence between family support and motivation to recover of the drug addicts (p=0,012, less than the value ɑ=0,05) and there were influence of counselor support on motivation to recover of the drugs addict by (p=0,000, less than the value ɑ=0,05). Finally, it can be concluded that there is influence of family and counselor support on motivation to recover for the drug addicts in the rehabilitation center of BNN Baddoka Makassar.